(untitled) (Journal of the Bangladesh Chemical Society, 2012)
Treatment of different aromatic primary amines (7a-b) with chloral hydrate andhydroxylamine hydrochloride under microwave (MW) conditions afforded correspondingisonitrosoacetanilides (6a-b). These intermediate compounds (6a-b) were cyclized inconc. H2SO4 medium to give cyclic amides (5a-b) by means of elcetrophilicaromatic substitution reaction. The microwave (MW) mediated treatment of compound5a with thiosemicarbazide afforded the corresponding Schiff-base 4a, which undergoescyclization to give thiadiazoline (1). Beside, compound 4a was also treated with aq KOHsolution under MW condition to give triazinothione (3). The Sn-HCl mediatedreduction of compound 3 afforded the corresponding 6-aminothione (2). On the otherhand, compound 5b was treated with o-phenylenediamine under MW condition to givethe corresponding quinoxaline derivative 4b in excellent yield. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11771 Journal of Bangladesh Chemical Society, Vol. 25(1), 46-52, 2012